Fundamental Legal Principles for Implementation of State Control over Land Use in the Russian Federation - LUTOVINOVA, Natalya Viktorovna; NEZNAMOVA, Alla Andreevna; GURYLEVA, Alexandra Andreevna; BOLSHAKOVA, Oksana Gennadyevna; SHMYREV, Denis Viktorovich (Journal of Advanced Research in Law and Economics; Vol 5 No 2 (2014): JARLE Volume V, Issue 2(10), Winter 2014, 2017)
In the modern legal science the issue of state control over land use in the Russian Federation is of particular interest and has diversity of views, as land users are not able to control their own behavior objectively and adequately, as well as voluntarily take steps to correct it, especially if it affects their financial and material interests. From the technical, organizational and material aspects, individual land users are not always able to organize some forms of modern control, such as monitoring of natural objects, by own efforts. It is impossible to ensure the unity of control activities, their coordination, analysis and evaluation, not creating special external organizational structures. The fight against offenses in this area requires outside intervention, such as state control. The objectives of the state land control are to ensure that individuals, officials and legal entities comply with the requirements of land legislation in order to effectively use and protect this land. State land control involves permanent work of relevant bodies, implemented in accordance with the departmental annual work plans. The required control actions are taken in case of applications and complaints filed by citizens. The objects under the state land control include the actions of all the subjects of the land legislation, individuals and legal entities associated with the exercise of the rights of ownership, possession, use, lease of land plots, measures to ensure their sustainable use and conservation. The independent object of state land control includes the actions of the officials exercising the functions on privatization and provision of land, registration of land rights and other administrative functions.